Paradigma Keadilan Struktural & Dialog: Reaktualisasi Yohanes XXIII Dalam Pacem In Terris Bagi Perdamaian Kontemporer - Sianturi, Krisna Ricardo; Riyanto, F.X Armada (Sekolah Tinggi Pastoral IPI Malang, 2025)
John XXIII’s encyclical Pacem in Terris (1963) offers profound reflections on the prerequisites for global peace, emphasizing structural justice and dialogue as fundamental pillars. This paper aims to reactualize John XXIII’s thought in the context of contemporary peace. Through a qualitative-analytical approach, this study analyzes the encyclical to extract principles of structural justice that demand transformative, inclusive political, economic, and social systems, as well as multidimensional dialogue as an instrument for conflict resolution. The findings reveal that John XXIII’s paradigm remains relevant, particularly in addressing the complexities of globalization, where systemic injustices and the absence of dialogue spaces often underlie violence. Structural justice is realized through the strengthening of equitable international law, the protection of human rights, and the fair distribution of resources, while dialogue is positioned as a medium to build empathy among fragmented groups. The study recommends integrating the values of Pacem in Terris into global and local policies. Thus, the reactualization of John XXIII’s thought transcends its theological legacy, serving as an operational framework for achieving sustainable peace amid modern societal dynamics.